Mengamankan Perangkat Jaringan Dari Serangan DDoS Menggunakan Fitur Firewall-RAW di Router MikroTik - Bahri, Syaiful; Purba, Doni El Rezen (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2024)
DDoS (Denial of Service) attacks are a serious threat in network security that can cause services to become unavailable due to unusually high traffic volumes. This research aims to secure network devices from DDoS attacks by using the Firewall-RAW feature on the MikroTik Router. In tests carried out using MikroTik RouterOS, DDoS attacks were effectively prevented by using firewall rules that were set to reject packets that exceeded a predetermined threshold. However, the test results also show that the CPU Load of the device is still affected by DDoS attacks, although to a limited extent. This emphasizes that protecting against DDoS attacks is not an easy task, but the use of firewall rules can help reduce the system load due to these attacks. The recommended next step is to ensure the router device has sufficient CPU resources to anticipate the impact of a DDoS attack that may occur in the future. However, it is important to remember that firewall rules are only an additional protective measure and do not guarantee absolute protection from DDoS attacks. Therefore, there is a need for a comprehensive security strategy and appropriate infrastructure improvements to reduce the risk of greater DDoS attacks